Effects of pulmonary fissure completeness on major outcomes in children after video-assisted thoracoscopic congenital lung malformation lobectomy - Jin-Xi Huang; Qiang Chen; Song-Ming Hong; Jun-Jie Hong; Hua Cao (BMC, 2022)
Abstract We performed a single-centre retrospective analysis using data from databases that were prospectively maintained in our centre between January 2019 and September 2021. Patients were divided into two groups based on the degree of pulmonary fissure completeness (PFC), using the fissure development scoring system. Patients with grades 2 or 3 PFC were considered to have incomplete pulmonary fissures and were included in Group A, and patients with grades 0 and 1 were considered to have complete pulmonary fissures and were included in Group B. The differences in demographics, perioperative characteristics and clinic outcomes between the two groups were evaluated. Multivariate logistic regression analysis was performed. A total of 213 patients with congenital lung malformation (CLM) underwent video-assisted thoracoscopic lobectomy. There were 30 patients in Group A and 183 patients in Group B. Our data showed that compared with Group B, Group A had a higher incidence of complications, especially Clavien-Dindo grade II and grade III complications. The degree of PFC was significantly correlated with the length of chest tube drainage and postoperative hospital stay. Multivariate logistic regression analysis showed that the degree of PFC could be used to predict the incidence of postoperative complications. Conclusions The degree of PFC is a predictor of the incidence of complications after thoracoscopic lobectomy in children with CLM.